RESEARCH RESULTS OF INSULIN RESISTANCE IN CHRONIC HEPATITIS C IN PATIENTS THROUGH THE TRIGLYCERID-GLUCOSE INDICATOR (Vietnam Journal of Community Medicine, 2022)
Objectives: Survey of insulin resistance through Triglyceride - glucose index and HOMA-IR index.Studying the relationship between insulin resistance according to Triglyceride - glucose index withsome risk factors in patients with chronic hepatitis C.Subjects and methods: Patients aged 18 years or older were diagnosed with chronic hepatitis Caccording to the criteria of the Ministry of Health in 2016, come for examination and treatment at theMedical Examination Department of Binh Thanh District Hospital from 5/2020 to 6/2021. Researchby a descriptive cross-sectional method.Results: The rate of insulin resistance according to Triglyceride - Glucose was 47.7%; HOMA-IRis 48.9%; The rate of insulin resistance according to Triglyceride - Glucose in cirrhosis group F4(Fibroscan) was 79.3%. There was a statistically significant relationship between the degree of liverfibrosis and insulin resistance according to Triglyceride - Glucose index (p
Keywords: Triglycerid - Glucose, insulin, Binh Thach hospital.